Implementing the School Management System through the Application in SDN 17 Rantau Utara - Petrus Sanjaya Simarmata; Nathanael Sitanggang; Joharis Lubis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The rapid development of information technology is a very important role in supporting educational institutions at SDN 17 Rantau Utara where the purpose of this research is to create an application system that can help schools in management. This study uses the faterfall method, the application system that has been created is used to store data related to schools, teachers, staff, students. The results of the research at SDN 17 Rantau Utara are expected to be able to improve the quality of application-based school management.